2016
DOI: 10.1038/srep36714
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear import of dimerized ribosomal protein Rps3 in complex with its chaperone Yar1

Abstract: After their cytoplasmic synthesis, ribosomal proteins need to be transported into the nucleus, where they assemble with ribosomal RNA into pre-ribosomal particles. Due to their physicochemical properties, they need protection from aggregation on this path. Newly synthesized ribosomal protein Rps3 forms a dimer that is associated with one molecule of its specific chaperone Yar1. Here we report that redundant pathways contribute to the nuclear import of Rps3, with the classical importin α/β pathway (Kap60/Kap95 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…As shown in Fig. 2B, uS5 was efficiently recovered in anti-GFP precipitates prepared from extracts of cells that expressed the WT version of ZNF277 (see lane 9). In contrast, a control purification prepared from extracts of cells that expressed GFP alone did not copurify uS5 (Fig.…”
Section: C2h2 Zinc Finger Domains Of Znf277 Are Important For the Assmentioning
confidence: 80%
“…As shown in Fig. 2B, uS5 was efficiently recovered in anti-GFP precipitates prepared from extracts of cells that expressed the WT version of ZNF277 (see lane 9). In contrast, a control purification prepared from extracts of cells that expressed GFP alone did not copurify uS5 (Fig.…”
Section: C2h2 Zinc Finger Domains Of Znf277 Are Important For the Assmentioning
confidence: 80%
“…2A, lanes 1, 3, 5, and 6). Kap123 is considered the primary importin for RPs (22), while Kap104 has been shown to interact with specific RPs (16,18,20,23). This result suggests that the Rps2 core is needed for the recruitment of an importin.…”
mentioning
confidence: 99%
“…We found that binding of importin α (Kap60 in yeast) competed with Yar1 for binding to Rps3, suggesting that one N-domain of Rps3 can only bind either importin or Yar1 (Figure 1, Step III). As we nevertheless detected complexes containing Rps3 and both Yar1 and Kap60 in vivo , Rps3-dimers with Yar1 bound to one and importin bound to the second Rps3 N-domain might represent the preferred conformation for nuclear import 5. It is still a puzzle how such architecture is retained, but assuming that the complex is imported immediately after one of the two Yar1 copies has been replaced by importin, the limited time for a second importin to access the second Rps3 copy might make it simply more likely that one Yar1 is maintained.…”
mentioning
confidence: 67%
“…NLSs comprise the binding sites for importins, which mediate the transport of proteins through the nuclear pores into the nucleus 6. Our analyses suggest that several redundant routes engage in Rps3 import, with major contribution from the classical importin α/importin β pathway 5. We found that binding of importin α (Kap60 in yeast) competed with Yar1 for binding to Rps3, suggesting that one N-domain of Rps3 can only bind either importin or Yar1 (Figure 1, Step III).…”
mentioning
confidence: 87%